Neonatal cardiomyopathy in mice homozygous for the Arg403Gln mutation in the α cardiac myosin heavy chain gene - Fatkin, Diane (American Society for Clinical Investigation, 1999)
Heterozygous mice bearing an Arg403Gln missense mutation in the α cardiac myosin heavy chain gene (α-MHC(403/+)) exhibit the histopathologic features of human familial hypertrophic cardiomyopathy. Surprisingly, homozygous α-MHC(403/403) mice die by postnatal day 8. Here we report that neonatal lethality is caused by a fulminant dilated cardiomyopathy characterized by myocyte dysfunction and loss. Heart tissues from neonatal wild-type and α-MHC(403/403) mice demonstrate equivalent switching of MHC isoforms; α isoforms in each increase from 30% at birth to 70% by day 6. Cardiac dimensions and function, studied for the first time in neonatal mice by high frequency (45 MHz) echocardiography, were normal at birth. Between days 4 and 6, α-MHC(403/403) mice developed a rapidly progressive cardiomyopathy with left ventricular dilation, wall thinning, and reduced systolic contraction. Histopathology revealed myocardial necrosis with dystrophic calcification. Electron microscopy showed normal architecture intermixed with focal myofibrillar disarray. We conclude that 45-MHz echocardiography is an excellent tool for assessing cardiac physiology in neonatal mice and that the concentration of Gln403 α cardiac MHC in myocytes influences both cell function and cell viability. We speculate that variable incorporation of mutant and normal MHC into sarcomeres of heterozygotes may account for focal myocyte death in familial hypertrophic cardiomyopathy.